Hepatobiliary transport in health and disease. (April 2012) - Chan, Jeannie; VandeBerg, John L
Bile salts, cholesterol and phosphatidylcholine are secreted across the canalicular membrane of hepatocytes into bile by ATP-binding cassette (ABC) transporters. Secretion of bile salts by ABCB11 is essential for bile flow and for absorption of lipids and fat-soluble vitamins. ABCG5 and ABCG8 eliminate excess cholesterol and sterols from the body by secreting them into bile. There are two mechanisms to protect the canalicular membrane from solubilization by bile salts; ABCB4 secretes phosphatidylcholine into bile to form mixed micelles with bile salts, and ATP8B1 maintains the canalicular membrane in a liquid-ordered state. Three different forms of progressive familial intrahepatic cholestasis (PFIC) disorders, PFIC1, PFIC2 and PFIC3, are caused by mutations in ATP8B1, ABCB11 and ABCB4, respectively. Sitosterolemia is caused by mutations in ABCG5 and ABCG8 . This article reviews the physiological roles of these canalicular transporters, and the pathophysiological processes and clinical features associated with their mutations.